1996
DOI: 10.1073/pnas.93.15.7528
|View full text |Cite
|
Sign up to set email alerts
|

COOH-terminal processing of nascent polypeptides by the glycosylphosphatidylinositol transamidase in the presence of hydrazine is governed by the same parameters as glycosylphosphatidylinositol addition.

Abstract: Proteins anchored to the cell membrane via a glycosylphosphatidylinositol (GPI) moiety are found in all eukaryotes. After NH2-terminal peptide cleavage of the nascent protein by the signal peptidase, a second COOH-terminal signal peptide is cleaved with the concomitant addition of the GPI unit. The proposed mechanism of the GPI transfer is a transamidation reaction that involves the formation of an activated carbonyl intermediate (enzyme-substrate complex) with the ethanolamine moiety of the preassembled GPI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 18 publications
1
29
0
Order By: Relevance
“…In contrast, depletion of intracellular levels of GPI protein anchor precursors by ectopic expression of T. brucei GPI-PLC in L. major resulted in the secretion of a hydrophilic form of gp63 (Mensa-Wilmot et al, 1994). Similarly, cleavage of the signal peptide without anchor addition has been reported in both mammalian and trypanosomal in vitro systems and resulted in the release of processed, but GPI-free, protein (Maxwell et al, 1995a;Ramalingam et al, 1996;Sharma et al, 1999). However, in the absence of the proteolytic processing event (as would be the situation in ⌬GPI8), the protein is targeted for degradation.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, depletion of intracellular levels of GPI protein anchor precursors by ectopic expression of T. brucei GPI-PLC in L. major resulted in the secretion of a hydrophilic form of gp63 (Mensa-Wilmot et al, 1994). Similarly, cleavage of the signal peptide without anchor addition has been reported in both mammalian and trypanosomal in vitro systems and resulted in the release of processed, but GPI-free, protein (Maxwell et al, 1995a;Ramalingam et al, 1996;Sharma et al, 1999). However, in the absence of the proteolytic processing event (as would be the situation in ⌬GPI8), the protein is targeted for degradation.…”
Section: Discussionmentioning
confidence: 95%
“…A third possibility is that the lytic secreted molecules may be generated by an aborted transamidation, in which cleavage of the polypeptide chain would be followed by reaction with a water molecule instead of the GPI anchor (17,44). Such a reaction was observed with the nucleophilic reagent hydrazine: by reacting with an intermediate of the transamidation reaction, hydrazine prevents the attachment of the GPI anchor and releases a cleaved, soluble protein.…”
Section: Fig 3 Relationship Between the Cellular Activity And The Nmentioning
confidence: 99%
“…The structural requirements of the C-terminal signal peptides that induce GPI addition have been investigated extensively by the groups of Caras and Udenfriend, by mutagenesis of the "decay-accelerating factor" (9 -12) and of placental alkaline phosphatase (13)(14)(15)(16)(17). They showed that glypiation requires a C-terminal hydrophobic sequence and an upstream cleavage/addition site (2,13).…”
mentioning
confidence: 99%
“…The transfer of preformed GPIs onto proteins has been studied in microsomal translation/translocation/GPI-anchoring systems (Ramalingam et al, 1996;Sharma et al, 1999) or translocation/GPI-anchoring systems (Doering and Schekman, 1997) in several organisms, and these studies allowed a preliminary biochemical characterization of the GPI transfer reaction. The GPI transferase is believed to act as a transamidase, i.e., to jointly remove the GPI-anchoring signal and transfer the preformed GPI (Ramalingam et al, 1996;Sharma et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The GPI transferase is believed to act as a transamidase, i.e., to jointly remove the GPI-anchoring signal and transfer the preformed GPI (Ramalingam et al, 1996;Sharma et al, 1999). Genetic approaches have identified genes required for the addition of GPI anchors.…”
Section: Introductionmentioning
confidence: 99%